Answer:
y = 6x + 43
Step-by-step explanation:
Our unknown line is of the form
y = kx + m
Where k is the slope of the line.
Since our line is parallel to 6x+1, the slope of the two lines must be equal. In other words, the two must have the same value of k.
In our line 6x+1, the k value is 6.
Thus, our unknown line must look like this:
y = 6x + m
Now, we need to find out what m is. Our line passes through (-7, 1).
Thus, we know that when x is equal to -7, y is equal to 1,
We can put these two values:
x = -7
y = 1
...into our line to find m.
y = 6x + m
1 = 6 * (-7) + m
Since 6 * (-7) = -42
1 = - 42 + m
1 = m - 42
Now, we can add 42 to both sides:
1 + 42 = m - 42 + 42
43 = m
m = 43
Our line has the k-value of 6, and m-value of 43. As such, the equation will be the following:
y = kx + m
y = 6x + 43
Answer: y = 6x + 43